2000
DOI: 10.1093/carcin/21.5.881
|View full text |Cite
|
Sign up to set email alerts
|

2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) inhibits growth factor withdrawal-induced apoptosis in the human mammary epithelial cell line, MCF-10A

Abstract: to TCDD from an industrial accident in Seveso, Italy did not Previous studies have demonstrated that 2,3,7,8-tetrachlororesult in increased incidence of breast cancer (4), while other dibenzo-p-dioxin (TCDD) increases cell recovery in the reports suggest that exposure to environmental contaminants human mammary epithelial cell line MCF-10A grown may increase risk of breast cancer (7). under growth factor-restricted conditions. TCDD was also Activation of growth factor receptors and their cognate found to mimic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…In mammary epithelial cells, TCDD is known to trigger EGFR signaling by induction of TGF␣ mRNA and protein (26,27). Studies using HeLa cells and MEFs have shown that TCDD suppresses the checkpoint protein MAD2 or induces MAPKs in an AhRindependent manner (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…In mammary epithelial cells, TCDD is known to trigger EGFR signaling by induction of TGF␣ mRNA and protein (26,27). Studies using HeLa cells and MEFs have shown that TCDD suppresses the checkpoint protein MAD2 or induces MAPKs in an AhRindependent manner (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…TCDD inhibits apoptosis in hepatocytes treated with UV light or 2-acetylaminofluorene, an effect that was also attributed in part to attenuation of p53 activity [Worner and Schrenk, 1996;Schrenk et al, 2004]. Apoptosis induced by growth factor withdrawal in human epithelial cells is inhibited by TCDD treatment, in correlation with activation of the EGF signaling pathway [Davis et al, 2000b]. Studies with AHR-null mice confirm the importance of the AHR in tissue homeostasis, as hepatocytes from these mice exhibit accelerated rates of apoptosis associated with increased production of TGF-b [Gonzalez and FernandezSalguero, 1998].…”
Section: Ahr-mediated Inhibition Of Apoptosismentioning
confidence: 99%
“…Although the role of AHR in determining apoptosis susceptibility is yet emerging (Gonzalez and Fernandez-Salguero, 1998;Reiners and Clift, 1999;Camacho et al, 2002;Park et al, 2005), much of the work in this area has been performed using conditions in which the AHR has been activated exogenously by TCDD, rather than by those that may mimic its endogenous role (Davis et al, 2000(Davis et al, , 2001Schrenk et al, 2004;Park et al, 2005). As reviewed recently by Marlowe and Puga (2005), the mechanisms by which the TCDD-activated AHR has thus far been proposed to alter apoptosis seems to involve the p53, EGFR, and/or TGF␤ signaling pathways.…”
mentioning
confidence: 99%